A new bone-cutting approach for minimally invasive surgery. (January 2021) - Minnaard, Jeffrey; Kleipool, Roeland P; Baars, Wim; Dankelman, Jenny; Stufkens, Sjoerd; Horeman, Tim
Highlights: The development of a minimally invasive bone sectioning method that can be used on multiple bone types Mechanical bone sectioning without damaging surrounding weak tissue during bone-cutting This new bone-cutting method features a new steerable wire saw placement device that can place a wire (saw) around the bone A support system that allows wire sawing of the bone while preventing contact between the moving saw and surrounding tissue Abstract: Aims: Resection of bone is performed in over 75% of all orthopaedic procedures and the electrically powered oscillating saw is commonly used to cut bone. Drawbacks are relatively large incisions and tissue damage due to overshooting often occur. Therefore, the goal of this study is to develop an improved bone-cutting system that has minimally invasive characteristics. Methods: A new reusable sawing system was designed that can be used in Minimally Invasive Surgery (MIS) consisting of a steerable wire passer and a tissue saving wire saw guide. The system was tested during surgery on a human cadaveric tibia and calcaneus. Results: A MIS steerable compliant Nitinol needle was built and successfully used in a cadaveric surgery to position the cutting wire around a tibia and calcaneus. A wire saw operating system was built that was successfully used to cut the tibia and calcaneus. Conclusion: A MIS bone-cutting system was successfully designed, manufactured and used in a cadaver study showing that safe minimally invasive bone-cutting is feasible for two bone types with minimal damage to the surrounding tissue. Design optimization is needed to stabilize the compliant Nitinol needle during wire saw positioning and to allow cutting of bones with smaller diameters. Graphical abstract: Image, graphical abstract